Rencana Keselamatan Konstruksi pada Proyek Pembangunan Gedung Bertingkat: Evaluasi dan Pengembangan - Indarta, Fhirtania Ashril; Soetjipto, Jojok Widodo; Ratnaningsih, Anik (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2025)
Multi-story building construction projects have high complexity, involving many stakeholders with different skills and competencies. Therefore this project has a threat of failing to comply with security, safety, health, and sustainability (K4) standards. The government requires each project development stage to implement a Construction Safety Plan (RKK), but in reality, many construction activities still need to pay attention to this standard. Therefore it is necessary to evaluate RKK implementation in construction projects to minimize construction accidents. This study aims to determine the implementation of construction safety planning stages in building projects. This research will take a case study of the Regent's Office Building Project and the Regional Secretariat of Pasuruan Regency by conducting direct observations and interviews to evaluate the implementation of the RKK. The study results show that all components of the RKK are available, but the analysis of the potential hazards that may occur still needs to be improved. Job safety analysis as a construction safety plan has yet to be supported by proper hazard identification, risk assessment, and risk control following the implemented implementation method. This research can use the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method to solve this problem. The results of the HIRARC method assessment adjusted for the available variables according to the project implementation method yielded the following results. There were 26 variables with low risk, 57 with medium risk, and 21 with high risk. The hazard risk control strategy is prepared based on the OHS risk control hierarchy, namely engineering control, administrative management, and provision of PPE, because almost all activities in building work do not allow for eliminating risks using elimination and substitution.